Integrated molecular and immunophenotypic analysis of NK cells in anti-PD-1 treated metastatic melanoma patients. (1st February 2019) - Lee, Hansol; Quek, Camelia; Silva, Ines; Tasker, Annie; Batten, Marcel; Rizos, Helen; Lim, Su Yin; Nur Gide, Tuba; Shang, Ping; Attrill, Grace H.; Madore, Jason; Edwards, Jarem; et al.
ABSTRACT: Purpose : Anti-PD-1 therapy has revolutionized the treatment and improved the survival of stage IV melanoma patients. However, almost half of the patients fail to respond due to immune evasive mechanism. A known mechanism is the downregulation of major histocompatibility complex (MHC) class I expression, which prevents T cell recognition of the tumor. This study determined the relationship between natural killer (NK) cell numbers and clinical response to anti-PD-1 therapy in metastatic melanoma. Experimental Design : Twenty-five anti-PD-1 treated metastatic melanoma patients were categorized into responders (complete response (CR)/partial response (PR)/stable disease (SD) ≥ 6 mo, n = 13) and non-responders (SD < 6 days/progressive disease (PD), n = 12) based on RECIST response. Whole transcriptome sequencing and multiplex immunofluorescent staining were performed on pre-treatment and on a subset of early during treatment tumor samples. Spatial distribution analysis was performed on multiplex immunofluorescent images to determine the proximity of NK cells to tumor cells. Flow cytometry was used to confirm NK phenotypes in lymph node metastases of treatment naïve melanoma patients (n = 5). Cytotoxic assay was performed using NK cells treated with anti-PD-1 or with isotype control and co-cultured with 3 different melanoma cell lines and with K562 cells (leukemia cell line). Results : Differential expression analysis identified nine upregulated NK cell specific genes (adjusted p < 0.05) in responding (n = 11) versus non-responding patients (n = 10). Immunofluorescent staining of biopsies confirmed a significantly higher density of intra- and peri-tumoral CD16+ and granzyme B + NK cells in responding patients ( p < 0.05). Interestingly, NK cells were in closer proximity to tumor cells in responding PD-1 treated patients compared to non-responding patients. Patients who responded to anti-PD-1 therapy, despite MHC class I loss had higher NK cell densities than patients with low MHC class I expression. Lastly, functional assays demonstrated PD-1 blockade induces an increase in NK cells' cytotoxicity. Conclusions : A higher density of tumoral NK cells is associated with response to anti-PD-1 therapy. NK cells may play an important role in mediating response to anti-PD-1 therapy, including in a subset of tumors downregulating MHC class I expression.